Automatically Tagging Entities with Descriptive Phrases - Chakrabarti, Kaushik; Chaudhuri, Surajit; Cheng, Tao; Xin, Dong (WWW (Poster paper), 2011)
We consider the problem of entity tagging: given one or more named entities from a specific domain, the goal is to automatically associate descriptive phrases, referred to as etags (entity tags), to each entity. Consider a product catalog containing product names and possibly short descriptions. For a product in the catalog, say Ricoh G600 Digital Camera, we want to associate etags such as “water resistant”, rugged” and “outdoor” to it, even though its name or description does not mention those phrases. Entity tagging can enable more effective search over entities. We propose to leverage signals in web documents to perform such tagging. We develop techniques to perform such tagging in a domain independent manner while ensuring high precision and high recall.